Risk factors for complications in elderly patients aged 85 years and over undergoing endoscopic biliary stone removal - Zhang, Da-ya; Zhai, Ya-qi; Zhang, Guan-jun; Chen, Sheng-xin; Wu, Lang; Chen, De-xin; Li, Ming-yang (Frontiers in Surgery, 2022)
Background and Aim: The number of elderly patients with biliary stones is increasing. Endoscopic retrograde cholangiography (ERCP) is considered to be an effective treatment for biliary stones. Having a sound knowledge of the risk factors can help reduce the incidence and severity of complications for ERCP. Furthermore, limited research has been published on patients aged over 85 years undergoing endoscopic biliary stone removal. This study aims to determine the risk factors that lead to complications of ERCP in patients over 85 years of age． Methods: This was a single-center retrospective study. We analyzed 156 patients aged ≥ 85 years with biliary stones who underwent their first ERCP at Chinese PLA General Hospital from February 2002 to March 2021. Logistic regression models were employed to identify the independent risk factors for complications. Results: A total of 13 patients (8.3%) had complications. Thereinto, pancreatitis, cholangitis, bleeding, and other complications occurred in 4 cases (2.6%), 1 cases (0.6%), 4 cases (2.6%), and 4 cases (2.6%), respectively. There was no perforation or death related to ERCP. Independent risk factors for complications were acute biliary pancreatitis (ABP) (P=0.017) and Charlson Comorbidity Index (CCI) (P=0.019). Significantly, reasons for incomplete stone removal at once were large stone (>10mm) (P<0.001) and higher acute physiology and chronic health evaluation scoring system (APACHE-II) (P=0.005). Conclusions: ERCP was recommended with caution in patients ≥ 85 years of age with ABP or higher CCI undergoing endoscopic biliary stone removal. In patients with ABP without cholangitis or biliary obstruction we recommend against urgent (within 48 hours) ERCP. Patients with higher CCI who can tolerate ERCP can undergo rapid ERCP biliary stenting or nasobiliary implantation with later treatment of stones, and patients who cannot tolerate ERCP are treated promptly with PTCD and aggressive conservative treatment.